Global Superconvergence of the Mixed Finite Element Methods for 2-D Maxwell Equations (Journal of Computational Mathematics, 2021)
Superconvergence of the mixed finite element methods for 2-d Maxwell equations is studied in this paper. Two order of superconvergent factor can be obtained for the $k$-th Nedelec elements on the rectangular meshes.
Keywords: Maxwell equations; Mixed finite element; Superconvergence; Postprocessing.